Polychaete Assisted Sand Filter In Treating Synthetic Wastewater - Baharudin , Nurul Syuhada (2014)

(untitled)
This study is about polychaete assisted sand filter in treating synthetic wastewater. To test the application of this concept, polychaete assisted sand filters were experimentally tested for their ability to treat synthetic wastewater. The main objective in this study was to examine the feasibility of polychaete assisted sand filter for synthetic wastewater filtration. Kajian ini adalah mengenai penuras pasir berbantukan polychaete dalam merawat air sisa tiruan. Untuk menguji aplikasi konsep ini, penuras pasir berbantukan polychaete digunakan bagi menguji keupayaan mereka untuk merawat air sisa tiruan. Objektif utama dalam kajian ini adalah untuk mengkaji keupayaan penuras pasir dengan kehadiran polychaete untuk penapisan air sisa tiruan.